Identifying and managing the factors needed to implement Benefits Realization Management frameworks in publicly funded innovation projects in South African context - Netshiswinzhe, Mashudu Keith (Department of Construction Economics and Management, 2022)
Innovation projects seeks to bring fourth new technology products or services to the marketplace (community) to respond to broader socio-economic challenges. Innovation projects have elements of complexity and uncertainty which often fails to meet stakeholder expectations. This requires the need to determine requirements which need to be considered while dealing with publicly funded innovation projects so as to ensure project benefits are realised. The objective of the study is to identify factors needed to implement Benefit Realisation Management (BRM) frameworks in managing publicly funded innovation projects. BRM framework was unpacked in assessing its role on publicly funded innovation in ensuring project benefits achievement. The framework was applied in assessing innovation projects within the Department of Science and Innovation (DSI). A qualitative research methodology was employed as to achieve the project objectives of the study. An in-depth approach was used through face to face interviews in collecting primary data from study respondents within the DSI. The study participants entailed project managers on two government level of authority, namely middle and senior management. The study output revealed the critical role of a BRM framework in achieving project benefits and meeting stakeholder's expectations. To ensure that project benefits are realised, factors such as project governance, return on investment, project success and value creation need to be taken into account. Furthermore, a relationship between BRM and business strategy need to co-exist for project benefits realisation. The BRM framework is essential and should play a central role in every project implemented. The framework quantifies the need for project stakeholders to embrace the modern approach of assessing projects without limiting it on the constraints of time, cost and quality also known as the iron triangle. Project should be assessed based on the impact and benefit derived and the BRM framework is a critical tool to effect it.